(3ehShYI HdOGf GdYGde HCdGQbGe (B/s - (3TQHd, ehQjS CSYOs; (3ceGd MfGs ((3HjQhJ (B:s (3OGQ GdacQ GdYQHj ,s, 1999)
(3JJfGhd gPg GdehShYI GdecKaI ehGVjY GdLZQGajG(B: (3GdHTQjI (B, (3GdGbJUGOjI (B, (3GdGbdjejI h gj JMJhj Ydi eSQO GaHGFj dcd HdOGf GdYGde eY NQjWI JhVM ehbY cd HdO aj bGQJg h GdeYdheGJ GdCSGSjI Yf gPG s
(3HjHdjhZQGajG(B:(3U(B.382s
Keywords: (3ehShYIs